The Effect Of Using Digital Storytelling On Students’ Intrinsic Motivation For Learning Vocabulary - Tri Jampi Setiyorini (Universitas Muhammadiyah Surabaya, 2020)
In elementary school, vocabulary is the key factors in language learning. However, many students still have a lack of intrinsic motivation in learning vocabulary. Thus, it affects their vocabulary mastery. To overcome this problem, the researcher uses the digital storytelling to improve students’ intrinsic motivation for learning vocabulary. This research aims at analyzing the effect of using digital storytelling on students’ intrinsic motivation for learning vocabulary and describing the benefits of digital storytelling to improve students’ intrinsic motivation for learning vocabulary. The type of this research is descriptive case study. The subjects of the study are 22 students of 2C of SD Teladan Yogyakarta in the academic year of 2017/2018. The researcher uses close-ended questionnaire and interview to collect the data. The study shows that there was significant difference before and after using digital storytelling towards students’ intrinsic motivation in learning vocabulary. From the result of the questionnaires, after using digital storytelling, students’ intrinsic motivation for learning vocabulary is higher. Based on the result of interviews, digital storytelling can improve students’ intrinsic motivation for learning vocabulary due to interesting media and exciting learning situation